Experiences of nutrition education by Nursing, remotely, in times of pandemic COVID-19 - da Silva, Carolina Vilela Santos; Gevú, Kamile Santos Siqueira; da Silva, Lucas Lima; Santos, Natália Cardoso da Silva; Freire, Jonathan Costa; Heringer, Maria Eduarda Alves; Palermo, Matheus Vidal Azevedo; Knupp, Virginia Maria Azevedo Oliveira; dos Santos, Janaina Luiza; Gevú, José Carlos Amaral (Seven Editora, 2023)
Nutrition education provides basic requirements for health promotion and protection; moreover, it enhances human growth and development with quality of life and citizenship. In this sense, the objective of this work was to guide students and the academic community - among other audiences - about proper nutrition in times of pandemic through social media and teleconsultation. To this end, an Instagram profile and a website called "nutrition in action" were created, in which several posts with various topics about food and health were made available. To enable nutritional guidance through teleconsultations, a material was built by the project team to guide nurses, nursing students, and nutritionists regarding the care provided in the nursing office. Given the amount of fake news and orientations diverging from the appropriate scientific literature, it was concluded that it is extremely relevant to guide the non-academic population about proper nutrition through digital media and teleconsultations.DOI: https://doi.org/10.56238/devopinterscie-093